Nolo's patents for beginners - Pressman, David, 1937-; Stim, Richard (Berkeley, CA : Nolo, 2021)
Provides an introduction to the patenting process, including information on invention documentation, patent searching, patent ownership, and patent infringement.
Introduction : your legal companion -- Patents and intellectual property law -- Qualifying for a patent -- Invention documentation -- Patent searching -- Reading and writing patents -- Patent prosecution and the pto -- Patent ownership -- Patent infringement -- International patent law -- Help beyond this book.
Includes index.
110243
Keywords: Patent laws and legislation -- United States -- Popular works; Patent practice -- United States; Law for laypersons; Popular works